A 12-month prospective cohort study of injury in international rowers. Issue 3 (21st August 2008) - Wilson, F; Gissane, C; Gormley, J; Simms, C
Abstract : Objective: In this study, the injury incidence and association with type and volume of training in international rowers were described. Design: A prospective cohort design was used over a 12-month period. Patients: 20 international rowers who were competing as part of the Irish Amateur Rowing Union squad system. Methods: The rowers were interviewed monthly, and data were collected regarding their training and competition exposure as well as their injury experience. Results: A mean injury rate of 3.67 per 1000 exposure hours was reported with a total of 44 injuries reported in a 12-month period. The mean number of injuries sustained per athlete was 2.2 (1.24) over the 12-month period. The area where the greatest number of injuries were reported was the lumbar spine (31.82% of total injuries, 95% CI 20 to 50) (fig 2) followed by the knee (15.91% of total injuries, 95% CI 10 to 30) and the cervical spine (11.36% of total injuries, 95% CI 5 to 24). Half of the injuries (22 injuries, 50% of total reported injuries) were to the spine (χ 2 = 30.8, df = 9, p = 0.0003). Ergometer training load was the most significantly associated with injury risk (r = 0.68, p = 0.01). Conclusion: International rowers are at higher risk of injury than most non-contact sports and some contact sports. The high risk of lumbar spine injury and the significant association of high volume of ergometer training merit further research to reduce time and competition lost to injury.